REPRESENTASI SIFAT DAN KEBIASAAN MASYARAKAT INGGRIS MELALUI TOKOH-TOKOH DALAM NOVEL NEMESIS KARYA AGATHA CHRISTIE - Wita Tania Nursalma (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2021)
Nemesis is a crime-fiction novel that was written by the queen of crime story, Agatha Christie, which published for the first time in Britain in 1971. Implicitly, this novel shows the Englishness that represented by the characters in the novel. The study tried to describe the characteristics and customs of English society through the characters in Agatha Christie’s Nemesis according to Fox (2014). The research method used is qualitative-descriptive. Content analysis is used to analyse the data. This study uses literary sociology approach in understanding the relationship between the social phenomena contained in the novel with the facts or realities that exist in society. The result of this study shows that most of the characters in the researched novel represent the characteristics and customs of English society, those are courteous; hypocritical; moderate; reserved; empirical; gardener; saying sorry, please, thank you; drinking tea; drinking alcohol, weather-talking; and reading newspaper.